Mašq-i qalam - Ṣiddīqī, Miṣbāḥ Aḥmad (Ejūkešnal Pablišing Hāʾūs, 2020)
Articles on Urdu literature.
Includes bibliographical references
Keywords: Aufsatzsammlung; Urdu literature; History and criticism.